ANALYSIS OF OPTIMIZATION OF TASK DISTRIBUTION AND WORKING TIME EFFICIENCY WITH THE HUNGARIAN METHOD APPROACH AT GLORY LAUNDRY - Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia; Rumansara, Marcko; Pasang, Deryanto; Ikakbur, Jesda; Pattikawa, Jeise D.F; Pujiastuty, Hesty; Adriaansz, Jeremy (Journal of Computer Science and Technology (JCS-TECH), 2025)
In response to the rapid development of business and increasingly intense competition, small businesses such as laundry services are required to manage time and task allocation efficiently to improve productivity. One of the laundry businesses facing this issue is the business owned by Mrs. Oktovina, located at Jl. A. M. Sangajai Gonof, Klawuyuk Subdistrict, Sorong City. The main problem encountered is the imbalance between the number of employees and the workload, resulting in ineffective task assignment and time management. To address this problem, the Hungarian Method was applied, which is known to be effective in solving optimal assignment problems. With the help of POM-QM software, the calculation process was carried out accurately to determine the most efficient work allocation for each employee. The calculation results showed that the optimal working time for Mrs. Oktovina is 15 minutes, Ima 30 minutes, and Sarman 5 minutes, bringing the total completion time to 50 minutes. The application of this method has proven to enhance work efficiency, accelerate task completion, and optimize employee productivity in providing better service to customers